2016
DOI: 10.1007/s10291-016-0564-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the antenna phase center models on the coordinates in the EUREF Permanent Network

Abstract: Precise positioning using the signals of the Global Position System requires correcting the distance between the points of reception of the signal carrier phase and the antenna reference point. Sophisticated models to account for these phase errors are available and widely in use. These models are usually based on calibrations of several antennas of the same type to derive a mean model. There is also the possibility of applying individual correction models that are derived for one single antenna, since the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…For these three specific hardware sets the individual calibrations are available at the EPN Central Bureau (ftp://epncb.oma.be/pub/station/general/epnc_08.atx). Switching between phase centre corrections from type mean to individual (or vice versa) causes a disagreement in the estimated up component of the stations, as was mentioned by Araszkiewicz and Voelksen (2017), and as a consequence in their ZTD time series. Depending on the antenna model, the offset at station KLOP in the up component (vertical displacement) is −5.2 ± 0.5, 8.7 ± 0.6 and 5.6 ± 0.8 mm with a corresponding offset in the ZTD of 0.2 ± 0.5, −1.5 ± 0.5, −1.4 ± 0.8 mm, respectively.…”
Section: Impact Of Glonass Datamentioning
confidence: 92%
“…For these three specific hardware sets the individual calibrations are available at the EPN Central Bureau (ftp://epncb.oma.be/pub/station/general/epnc_08.atx). Switching between phase centre corrections from type mean to individual (or vice versa) causes a disagreement in the estimated up component of the stations, as was mentioned by Araszkiewicz and Voelksen (2017), and as a consequence in their ZTD time series. Depending on the antenna model, the offset at station KLOP in the up component (vertical displacement) is −5.2 ± 0.5, 8.7 ± 0.6 and 5.6 ± 0.8 mm with a corresponding offset in the ZTD of 0.2 ± 0.5, −1.5 ± 0.5, −1.4 ± 0.8 mm, respectively.…”
Section: Impact Of Glonass Datamentioning
confidence: 92%
“…It should be remembered here that antenna modeling impacts on all estimates, such as tropospheric delay or clocks. However, previously conducted studies on receiver antennas show that the greatest impact of using different PCCs is more visible in the height [ 23 ], and much less visible in the tropospheric parameters [ 34 , 35 ]. Therefore, in our study, we focused only on the coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…An example is the calibrations performed by the University of Bonn, Institute of Geodesy and Geoinformation [ 20 ]. The compatibility between chamber calibrations and robot calibrations is on a millimeter level [ 18 ], and is constantly the subject of discussion and analysis [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noting the relationship between antenna models and differences between calibration results, they formulated recommendations for all relevant antennas. Araszkiewicz and Völksen (2017) compared type mean and individual antenna calibration models and demonstrated that for some antennas, the discrepancy in the position resulting from the utilized calibration model can reach 10 mm in both horizontal and vertical components. However, for most antennas, these offsets did not exceed 2-mm horizontal and 4-mm vertical components, respectively.…”
Section: Introductionmentioning
confidence: 99%